Scoping review of employment resources for individuals with fetal alcohol spectrum disorder and justice involvement - James P Fitzpatrick; Carmela F Pestell; Marie M A Nankoo; Kirsten R Panton (BMJ Open)
Objectives Individuals with fetal alcohol spectrum disorder (FASD) are over-represented within the justice system and have significant employment challenges. The primary aim of this scoping review was to ascertain available employment resources for FASD individuals particularly those involved in the justice system. Secondary aims were to determine available evidence-based interventions for the justice workforce and employment providers.Methods Eligibility criteria: That the resource was (a) published between 1990 and 2021, (b) in English, (c) available electronically in full text, (d) focused on strategies for improving employment outcomes of individuals with FASD and (f) developed for those aged over 15. Sources of evidence: Electronic searches of the following databases were conducted: EMBASE, MEDLINE, PsycINFO, Scopus, Web of Science and Google Scholar. Grey literature was collected via the databases ProQuest Dissertations & Theses Global, OpenGrey, GreyNet International and Grey Matters. Charting methods: Using Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews reporting guidelines, a five-stage methodological framework was employed. A quality appraisal of identified resources was conducted. Data were summarised qualitatively using a content analysis method that allowed for analysis of specific terms/themes/concepts/resource elements that resources covered, as well as a quantitative analysis of their frequency.Results An initial search identified 850 articles, 512 of which were obtained through online database searches, 321 through Google Scholar searches and 17 through google searches. Sixteen resources were identified as meeting inclusion criteria, including four peer-reviewed papers and 12 grey literature resources. Six of the resources extracted were deemed ‘good’ or ‘strong’ quality, with the remainder—all grey literature resources—being ‘adequate’ or ‘limited’. None of the resources identified were empirically evaluated or could be implemented synergistically. Content analysis revealed common themes addressing FASD-related employment challenges and required supports.Conclusions This review highlights the need for developing evidence-based employment-related resources for justice-involved people with FASD. Most of the 16 identified resources had a psychoeducational and advocacy component and described typical employment challenges with specific supports and accommodations to maximise workforce participation. However, none had been empirically evaluated, underscoring the importance of future research in this area to better inform more responsive and evidence-based employment-related programmes.Trial registration number doi:10.17605/OSF.IO/J5VMB.